No Evidence of Hepatitis C Virus (HCV)–Assisted Hepatitis D Virus Propagation in a Large Cohort of HCV-Positive Blood Donors. (17th August 2020) - Cappy, Pierre; Lucas, Quentin; Kankarafou, Nakourogou; Sureau, Camille; Laperche, Syria
Abstract: A study reported in 2019 showed that hepatitis C virus (HCV) could help disseminate hepatitis D virus (HDV). To test this finding, 2123 plasma samples positive for anti-HCV antibody were screened for anti-HDV antibodies, and HDV-RNA was searched for in samples positive for anti-HDV antibody. Of 41 samples (1.9%) that tested positive for anti-HDV antibody, 27 (65.9%) were positive and 14 (34.1%) negative for antibody to hepatitis B core antigen (anti-HBc). Anti-HDV antibodies were significantly more present in samples positive for anti-HBc (6.21% vs 0.8% in negative samples; P < .001) and in samples negative for HCV RNA (2.9% vs 1.5% for positive samples; P = .03). Serological ratios were significantly higher in samples positive for anti-HBc ( P < .01). No anti-HDV–positive sample was HDV RNA positive. In conclusion, this study found no evidence suggesting a role for HCV in HDV dissemination in humans. Abstract : After a study showing that hepatitis C virus (HCV) helped disseminate hepatitis D virus (HDV) in a liver-humanized mouse model, we screened a large cohort of HCV-positive blood donors for HDV markers and found no evidence of HCV-assisted propagation in humans.